Ovarian function of Nelore heifers fed a diet supplemented with rumen-protected fat - Guardieiro, Monique Mendes; Bastos, Michele Ricieri; Mourão, Gerson Barreto; Carrijo, Luiz Henrique Dantas; Melo, Eduardo de Oliveira; Rumpf, Rodolfo; Sartori, Roberto (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to evaluate the effect of rumen-protected fat supplementation on ovarian structures and on serum progesterone concentration in Nelore heifers kept in pasture. Forty heifers were divided into two groups: one supplemented with rumen-protected fat Megalac-E (F); and another without fat supplement (C). The groups were evaluated in a crossover design. The diets were isocaloric and isoproteic. After 15 days of supplementation, the animals were submitted to a hormonal protocol to evaluate the influence of fat supplementation on progesterone metabolism. For this, on a random day of the cycle (D0), the heifers received an intravaginal progesterone-releasing device (CIDR) and an injection of prostaglandin F2á (PGF2á, im). On D7, CIDR was removed and another injection of PGF2á was performed. On D18, a new treatment with PGF2á was done and, then, daily observations of estrus and ovarian ultrasound exams were carried out. For progesterone assay, blood samples were collected 4 days after CIDR insertion, and 7 and 14 days following ovulation. Serum progesterone concentration on D4 was higher for Group F. There was no difference between groups for serum progesterone concentration at 7 or 14 days following ovulation, neither in the ovulatory follicle, nor in the corpus luteum volume. Supplementation with Megalac-E alters progesterone metabolism, but does not affect ovarian function in zebu heifers kept in pasture.
Keywords: Bos indicus; fatty acids; corpus luteum; follicle; progesterone